Metabolomics of ethnic fermented foods and beverages: understanding new aspects through Omic techniques - Sarkar, Sagnik; Sha, Shankar Prasad; Ghatani, Kriti (Frontiers in Sustainable Food Systems, 2023)
In the era of Omics, metabolomics and metaproteomics have emerged as powerful tools for the deep analysis of the fermentation of various foods. These two are relatively new in the field of science. However, they are already proven to be crucial for a more proper understanding of microbes, their interactions with hosts and surrounding environments, metabolic activity, and intracellular biochemical reactions. Metabolomics is a quantitative and qualitative determination study of metabolites of participated microbes in the process of fermentation that helps to analyze several biochemical pathways concerning chemical changes that occur during different stages of fermentation. Hence, it provides a deep insight into the microscopic world as well as helps to significantly enhance the available nutraceuticals and probiotic characterizations in fermented foods. Evaluating the possible pathways of microbes in generating particular compounds of interest is proven to be beneficial for increasing the bioavailability of nutraceuticals and nutrients. It can be utilized to reshape the general process of fermentation in a more improved and optimized way for better yielding of nutritive components while decreasing the antinutrient components in the specific product. Metabolomics studies can be used to modify strains based on specific needs, for example, different stress-tolerant microbial strains for the optimal production of desired metabolites in stressed conditions, modulation in metabolic pathways to naturally increase the bioavailability of beneficial compounds, etc. These “Omics” methods are paving the way for a more thorough understanding of microbial life, metabolism systems, and genetic characteristics regarding protein synthesis and are undoubtedly becoming a potent weapon or a universal key in modulating fermented food products in a more advanced and sustainable approach possible. This present review aims to constitute a relevant approach for understanding the metabolic processes that can occur or are currently occurring in a given system and for implementing novel strategies focused on solving production problems or improving sustainability.